The relationship between adherence to therapy and the style of communicative interaction of the attending physician and patients undergoing coronary artery bypass graft - S. A. Pomeshkina; A. V. Solodukhin; A. A. Bezzubova; M. S. Yanitsky; O. L. Barbarash (Российский кардиологический журнал)
Aim. To study the communicative characteristics of the attending physician, assessed by the patient, and analyze their connection with adherence to the treatment of patients with coronary artery disease (CAD) undergoing coronary artery bypass graft (CABG).Material and methods. The study included 366 patients — men aged 41 to 77 years old (mean age 59,9±6,9 years) with a stable form of CAD. The patients included in the study were examined 57 days before the CABG and 6 months after it. The clinical condition of the patient, the presence of cardiovascular risk factors and the therapy taken before and within 6 months after were assessed. Before being discharged from the clinic, A. А. Leontiev communication card was used to determine the model of communicative interaction.Results. The higher the patient assessed the communicative competence of the doctor according to the several parameters (“benevolence”, “encouragement of initiative”, “openness”, “activity” and “flexibility”), the higher his adherence to treatment was. Patients who gave a low rating to the attending physician by the communicative parameters (“openness”, “flexibility” and “interest” in communication), had the lowest adherence to treatment.Conclusion. The adherence to treatment of CAD patients is influenced by such communicative characteristics of the attending physician as “benevolence”, “encouragement of initiative”, “openness”, “activity” and “flexibility” qualify as democratic style of communication between a doctor and a patient.